STUDI KOMPARATIF TENTANG ASAS LEGALITAS BERDASARKAN HUKUM PIDANA POSITIF INDONESIA DAN HUKUM PIDANA ISLAM - Leni Dwi Nurmala (Program Studi Magister Hukum Universitas Malikussaleh, 2021)
The purpose of this study is to determine the legality principle according to positive criminal law in Indonesia and Islamic criminal law and to find out the comparison between the legality principle according to positive criminal law and Islamic criminal law. This type of research used in this research is using library research or known as literature research. The principle of legality in Indonesia's positive criminal law is a very fundamental principle. Because the principle of legality in criminal law is important to determine whether a criminal law regulation can be treated against a criminal act that occurs. In Islamic criminal law, the legality principle has a great influence on the judge's power, because the judge's power is very broad compared to the judge in positive law where the judge does not have sufficient power to act against the crime maker in accordance with the public interest. Comparison of the principle of legality between Islamic law and positive law. Whereas the application of the legality principle to positive criminal law and Islamic criminal law has similarities and differences. The similarity is that both apply the principle of legality in the legal process while the difference is that positive criminal law is the same in its application to offenses, whereas in Islamic criminal law there is a distinction between Jarimah qishas diyat, hudud, which is applied strongly, while in Jarimah ta'zir it is relaxed so that the benefit of society is fulfilled. In addition to having the similarities and differences above, the legality principle also has advantages and disadvantages, among others, in Islamic law the criminal provisions cannot be changed (added / reduced) because it is a provision from Allah which is standard, while in positive law the criminal provisions may change at any time. according to the times.